Dual‐Color‐Emitting Carbon Nanodots for Multicolor Bioimaging and Optogenetic Control of Ion Channels. Issue 11 (3rd October 2017) - Kim, Hyemin; Park, Yoonsang; Beack, Songeun; Han, Seulgi; Jung, Dooyup; Cha, Hyung Joon; Kwon, Woosung; Hahn, Sei Kwang
Abstract: The development of intrinsically multicolor‐emitting carbon nanodots (CNDs) has been one of the great challenges for their various fields of applications. Here, the controlled electronic structure engineering of CNDs is performed to emit two distinct colors via the facile surface modification with 4‐octyloxyaniline. The so‐called dual‐color‐emitting CNDs (DC‐CNDs) can be stably encapsulated within poly(styrene‐ co ‐maleic anhydride) (PSMA). The prepared water‐soluble DC‐CNDs@PSMA can be successfully applied to in vitro and in vivo dual‐color bioimaging and optogenetics. In vivo optical imaging can visualize the biodistribution of intravenously injected DC‐CNDs@PSMA. In addition, the light‐triggered activation of ion channel, channelrhodopsin‐2, for optogenetic applications is demonstrated. As a new type of fluorophore, DC‐CNDs offer a big insight into the design of charge‐transfer complexes for various optical and biomedical applications. Abstract : A dual‐color‐emitting carbon nanodot (DC‐CND) is successfully developed by the facile surface modification with 4‐octyloxyaniline to emit two distinct colors according to the excitation wavelength. The biocompatible DC‐CNDs show the great potential for multicolor bioimaging and the optogenetic control of channelrhodopsin‐2.